El Líbano: crisol de culturas y pequeño Próximo Oriente - Corral, Carlos; Priego, Alberto (UNISCI Discussion Papers, 2007)
The continuous conflicts and multiple attempts at solving them, including the international mediations by the UN, the states or the Holy See, cannot be understood without taking into account the country’s cultural greatness and geographic smallness, as well as the complexity induced by them. Therefore, we explain this complexity in an article written before the latest international mediations.